Setup of a cryobank for ovarian tissue in a university-based setting - Baston-Büst, Dunja M.; Scheliga, Iwona; Bielfeld, Alexandra P. (Frontiers in Endocrinology, 2023)
Establishing and maintaining a newly set up cryobank in a university setting needs at least one year notice to start financial, spatial, lab equipment and acquisition of employees planning. Right before and after the start of the cryobank, the newly founded team should introduce itself to the hospitals´, local and national health system via mail, print flyers and symposia in order to share the possibilities and the knowledge. Potential referrers should be provided with standard operating procedures and advices to get used to the new system. Especially in the first year after the establishment, all procedures should be internally audited in order to face possible difficulties.